2022
DOI: 10.2147/jmdh.s341700
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Knowledge and Potential Determinants of COVID-19 Vaccine Acceptability Among University Students in the United Arab Emirates: Findings and Implications

Abstract: Objective: To evaluate the prevalence, knowledge, attitude and acceptance of the COVID-19 vaccines and related factors among university students in the United Arab Emirates. Methods: Analytical cross-sectional study undertaken among a convenient sample of medical and non-medical colleges of Ajman University using a self-administrated questionnaire. The questionnaire included demographic data as well as assessing knowledge of COVID-19, attitudes and acceptance of COVID-19 vaccines. Results: A total of 467 stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 80 publications
4
21
1
2
Order By: Relevance
“…Near to half 176 (43.8%) 95% CI: 39.1; 48.5 of the respondents were either refused or hesitated to receive COVID-19 vaccine. This finding matched the findings of studies in France (58.1%), 40 USA (53%), 37 USA (52.8%), 33 Nigeria (55.5%), 41 UAE (56.3%), 42 Libya (60.9%), 13 and Algeria (53.51%). 24 The current finding was lower than the study conducted in Italy (86.1%), 43 Canada (77.8%), 44 16 countries (69.2%), 45 Italy (91.9%), 46 and Ethiopia (69.3%).…”
Section: Discussionsupporting
confidence: 88%
“…Near to half 176 (43.8%) 95% CI: 39.1; 48.5 of the respondents were either refused or hesitated to receive COVID-19 vaccine. This finding matched the findings of studies in France (58.1%), 40 USA (53%), 37 USA (52.8%), 33 Nigeria (55.5%), 41 UAE (56.3%), 42 Libya (60.9%), 13 and Algeria (53.51%). 24 The current finding was lower than the study conducted in Italy (86.1%), 43 Canada (77.8%), 44 16 countries (69.2%), 45 Italy (91.9%), 46 and Ethiopia (69.3%).…”
Section: Discussionsupporting
confidence: 88%
“…We found that only 44.6% of the participants knew about the booster dose, meaning that more than half of the participants had a low knowledge level on this issue. A substantial body of prior research has established a similar lack of knowledge about COVID-19 vaccines [ 35 , 43 – 45 ]. In the present study, this lack of knowledge may be linked to the lack of information dissemination by the government among the public on the importance of taking the vaccine, particularly the booster dose.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research in the UAE found that the vaccine acceptance rate was influenced by concerns about unforeseen problems (65.5%), unforeseen impacts (35.1%) and general mistrust (47.3%) [ 35 ]. These concerns tended be linked to the potential side effects of the vaccine as well as the limited availability of trial data assessing its benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside this, appropriately trained pharmacists can assist with the instigation of ASPs, as well as educational initiatives generally, in ambulatory care to improve future antimicrobial prescribing 43,44 . Healthcare professionals, including community pharmacists, can also help address issues of vaccine hesitancy and other key issues going forward starting with appropriately trained medical and pharmacy students 45,46 .…”
mentioning
confidence: 99%